Implementasi Algoritma K-Means Clustering Pada Analisis Penyebaran Penyakit Pasien Pengguna Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) - Silitonga, Parasian D P; Damanik, Romanus (Jurnal Teknik Informatika UNIKA Santo Thomas, 2016)
Abstract Clustering technique is a technique of grouping of records in a database based on certain criteria. The clustering results are given to the end user to provide a snapshot of what is happening in the database. One method that can be used in clustering technique is a method of K-Means Clustering. K-Means Clustering method divides the data into multiple groups and can accept input in the form of data without a label. This study used the method K-Means Clustering data disease patients in an effort to find the tendency of the disease in a group of people who went to Haji Adam Malik Hospital in Medan. The results of this study are expected to be used as a reference for health education programs at once may be the anticipation of a priority service for patients especially BPJS users.